Influence of School Culture on Students’ Academic Performance in Public Secondary School in Gwagwalada Area Council of FCT, Abuja, Nigeria - Audu Elizabeth Iyabode (International Journal on Integrated Education, 2021)
The aim of the study was to find out the influence of school culture on students’ academic performance in public secondary school in Gwagwalada Area Council of FCT, Abuja, Nigeria. Result revealed that majorities of the respondents agreed that school culture influences good reading culture, class attendance, doing of assignments and home works, students’ culture of going for academic excursion, students’ preparation for continuous assessments, students preparation for exams, parents buying recommended textbooks for their wards (students) and that the school culture influences student –students collaboration and students’ academic performance in public secondary schools in Gwagwalada area council of FCT.